Anthropogenic impact on intraspecific ecological-temporal differentiation and structure of populations of pacific salmons - Vyacheslav N. Ivankov; Elena V. Ivankova (Известия ТИНРО)
Intraspecific temporal differentiation and population structure should be accounted in fishery, artificial breeding and introduction of anadromous species to provide stability of their ecological and genetic structure and maintain their high abundance. There is shown for the case of pacific salmons that ignoring of the population structure causes decreasing of the populations and distortion of their natural structure.